Electron-Impact Widths and Shifts of B III 2p-2s Lines - Bin Duan; Muhammad Abbas Bari; Zeqing Wu; Jun Yan (Atoms, 2014)
In this paper, we present results for the relativistic quantum mechanical calculations of electron-impact line widths and shifts of 2p-2s transitions in doubly ionized boron (B III) ions. We use the Dirac R-matrix methods to solve (N + 1)-electron colliding systems for the scattering matrices that are required. The line widths are calculated for an electron density 1:81 × 1018 cm-3 and electron temperature 10:6 eV. The obtained results agree well with all the semiempirical calculations and most of the semiclassical calculations, and are closer to the experimental results published by Glenzer and Kunze (Glenzer, S.; Kunze, H.-J. Stark broadening of resonance transitions in B III. Phys. Rev. A 1996, 53, 2225–2229). Our line widths are almost twice as large as the earlier quantum mechanical calculations for the set of particular plasma conditions.